PENGARUH KECERDASAN EMOSIONAL, DISIPLIN KERJA DAN KEPERCAYAAN DIRI TERHADAP KINERJA KARYAWAN PADA UD TOKO KARTIKA - Kiki Suryani Oktavia; Ni Nyoman Suryani; I Nyoman Mustika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
Human Resources are aspects related to employee performance. Performance is important for the entire organization because performance will determine the effectiveness of the organization. Performance is also important because performance is considered a measure of a manager's success in managing the organization and its human resources. This study aims to determine the effect of emotional intelligence on employee performance, the effect of work discipline on employee performance, the effect of self-confidence on employee performance at UD Toko Kartika. The sample in this study were all employees totaling 35 people. Data analysis using multiple linear regression analysis techniques to answer the problem formulation with the help of the SPSS program. The results of testing the hypothesis show that the variables: 1) Emotional intelligence has a positive and significant effect on employee performance 2) Work discipline has a positive and significant effect on employee performance 3) Self-confidence has a positive and significant effect on employee performance.